Single-cell RNA-seq revealing the immune features of donor liver during liver transplantation - Shan, Yi; Qi, Debin; Zhang, Lei; Wu, Lixue; Li, Wenfang; Liu, Hao; Li, Tao; Fu, Zhiren; Bao, Haili; Song, Shaohua (Frontiers in Immunology, 2023)
Immune cells, including T and B cells, are key factors in the success of liver transplantation. And the repertoire of T cells and B cells plays an essential function in mechanism of the immune response associated with organ transplantation. An exploration of their expression and distribution in donor organs could contribute to a better understanding of the altered immune microenvironment in grafts. In this study, using single-cell 5’ RNA sequence and single-cell T cell receptor (TCR)/B cell receptor (BCR) repertoire sequence, we profiled immune cells and TCR/BCR repertoire in three pairs of donor livers pre- and post-transplantation. By annotating different immune cell types, we investigated the functional properties of monocytes/Kupffer cells, T cells and B cells in grafts. Bioinformatic characterization of differentially expressed genes (DEGs) between the transcriptomes of these cell subclusters were performed to explore the role of immune cells in inflammatory response or rejection. In addition, we also observed shifts in TCR/BCR repertoire after transplantation. In conclusion, we profiled the immune cell transcriptomics and TCR/BCR immune repertoire of liver grafts during transplantation, which may offer novel strategies for monitoring recipient immune function and treatment of rejection after liver transplantation.